Heat shock protein 27 regulates human prostate cancer cell motility and metastatic progression - Voll, Eric A (Impact Journals LLC, 2014)
Prostate cancer (PCa) is the most common form of cancer in American men. Mortality from PCa is caused by the movement of cancer cells from the primary organ to form metastatic tumors at distant sites. Heat shock protein 27 (HSP27) is known to increase human PCa cell invasion and its overexpression is associated with metastatic disease. The role of HSP27 in driving PCa cell movement from the prostate to distant metastatic sites is unknown. Increased HSP27 expression increased metastasis as well as primary tumor mass. In vitro studies further examined the mechanism of HSP27-induced metastatic behavior. HSP27 did not affect cell detachment, adhesion, or migration, but did increase cell invasion. Cell invasion was dependent upon matrix metalloproteinase 2 (MMP-2), whose expression was increased by HSP27. In vivo, HSP27 induced commensurate changes in MMP-2 expression in tumors. These findings demonstrate that HSP27 drives metastatic spread of cancer cells from the prostate to distant sites, does so across a continuum of expression levels, and identifies HSP27-driven increases in MMP-2 expression as functionally relevant. These findings add to prior studies demonstrating that HSP27 increases PCa cell motility, growth and survival. Together, they demonstrate that HSP27 plays an important role in PCa progression.